The Works of Peter Schott, 1460-1490, Vol. I Introduction and Text - Cowie, Murray A.; Cowie, Marian L. (UNC Studies in the Germanic Languages and Literatures, 1963)
This first complete modern edition of Peter Schott's "Lucubraciunculae" opened a treasure-trove of information to students of German literature, historians of Humanism, folklorists, and theologians on its publication in 1963. Also included in this volume are the "De mensirus syllabarum epithoma" and a letter in German to Schott's sister Anna. Schott's works shed light on social, historical and religious questions of the time and are valuable documents of the Northern Renaissance.